Analisis Pajak Daerah Bea Balik Nama Kendaraan Bermotor dan Tingkat Risiko pada Masa Pandemi Covid-19 di Provinsi Bali - I Ketut Darma (Universitas Pendidikan Ganesha, 2021)
The purpose of this study is to calculate the potential and target of local tax revenue in Bali Province in 2021, especially BBNKB. Furthermore, this study is expected to be of benefit to the Bali Provincial Government (Bappenda) as a material for consideration in planning local tax revenue in the context of preparing the Bali Province Regional Revenue and Expenditure Budget Plan (RAPBD) for 2021. This study only calculates the potential for regional taxes, and calculating the target of regional tax revenue for 2021, in the form of Transfer of Motor Vehicle Title Fee (BBNKB). Calculating the estimated potential local taxes is done in an aggregate manner using secondary data available from the relevant agencies, especially at the Bali Provincial Bappenda, BPS, GAIKINDO, AISI and several other relevant internet sources. This aggregate estimate gives an indication of how much potential there is to be realized. followed by studies / policies on a micro basis in order to identify obstacles (risks) in the field and economic and non-economic factors with trend analysis and multiple linear regression. Thus, based on the theoretical basis, it is hoped that the local government will be able to make specific policies to bring the potential into realization. The results of this study indicate that the results of calculations using four methods yield different results, but the differences are not very significant. The results of this analysis are used as material for Bapenda's consideration in determining the BBN_KB I target for 2021. The achievement of tax potential estimates becomes a realization very much depends on policies and human resource capabilities.